Talkshow Online sebagai Bentuk Peran MUI dalam Pemulihan Karakter Keluarga di Masa New Normal: Online Talkshow as a Form of MUI's Role in Restoring Family Character in the New Normal Period - Masnawati Masnawati; Haniah Haniah; Sitti Saleha Madjid; Indo Santalia; Eka Damayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The research objective is to provide participants with provision, knowledge, and skills about the importance of maintaining attachment in the family, especially in the new normal era. The activity of the research was in the form of a talk show titled